RELIGIUSITAS TRANSFORMATIF DALAM GURIT BANDHA DONYA (KAJIAN ANTROPODIDAKTIS) - Sri Sulistiani (Universitas Negeri Surabaya, 2019)
Questioning about religious education in literature related to divinity and religiosity. Religiosity includes belief in God, belief in supernatural powers over humans, and belief in animism and dynamism. One of the media for religious education is through literary works. The author and / or poet with the sensitivity possessed captures religious symbols and the value of faith which then transforms them into a series of words into verses of poetry. The content of beauty and the meaning in literary works reflects the religiosity experience of the author and / or the poet. Regarding faith education in literature, the focus of the problem is how transformative religiosity in Gurit Bandha Donya and how the anthropodidactic value in Gurit Bandha Donya. To answer the problem, it is done through descriptive analysis and content analysis.